Modeling Routing Processes through Network Theory: A Grammar to Define RDEVS Simulation Models - Blas, María J.; Espertino, Clarisa; Gonnet, Silvio (Anais do Workshop em Modelagem e Simulação de Sistemas Intensivos em Software (MSSiS); 2021: Anais do III Workshop em Modelagem e Simulação de Sistemas Intensivos em SoftwareDO - 10.5753/mssis.2021.17255, 2021)
The Routed DEVS (RDEVS) formalism provides a reasonable formalization for the simulation of routing processes. In this paper, we introduce a context-free grammar for the definition of routing processes as a particular case of a constrained network model. Such grammar is based on a metamodel that defines the semantics over the syntactical elements. This metamodel allows a direct mapping between its concepts and RDEVS simulation models. A Java implementation is provided for the grammar as a plug-in for Eclipse IDE. The main benefit of this software tool is the feasibility of getting a simulation model without having programming skills.